Adaptasi dan Validasi Awal Alat Ukur Sikap Membuang Sampah Sembarangan (Littering Attitude Scale) ke dalam Versi Bahasa Indonesia - Muliadi, Rahmad; Jatnika, Ratna; Hanami, Yuliana (UIR Press, 2025)
Litter is one of the most important environmental problems to be addressed. Because the problem is very complex, the efforts made must be comprehensive and involve many parties. Several researchers stated that public attitudes towards the phenomenon of littering itself are important to study, because it can be one of the factors that determine whether someone will litter or not. By following the guidelines of the International Test Commission, this study aims to translate and adapt into Indonesian the